Like diamonds in the sky: how feedback can boost the amount of available data for learning analytics. (1st January 2013) - Mazarakis, Athanasios
This paper examines the role of feedback in the area of learning analytics. It introduces three different types of feedbacks, which enhance the motivation to play a learning game significantly longer than without feedback. A field experiment with 55 subjects has been conducted and evaluated to support these assumptions. Finally, the paper details the large number of open research questions in this area.